Pengaruh Motivasi dan Budaya Organisasi terhadap Kinerja Pegawai pada Dinas Komunikasi dan Informatika Kabupaten Seram Bagian Barat - Mandaku, Natalia; Zacharias, Tehubijuluw; Laurens, Samson (Jurnal Ilmiah Global Education, 2025)
This study aims to determine and analyze the influence of motivation and organizational culture on employee performance at the Department of Communication and Informatics of West Seram Regency. The research method used is a quantitative approach with an explanatory research type. The population in this study was 35 people, consisting of civil servants and honorary employees. A saturated sampling technique was used, considering the entire population was included as respondents. Data analysis techniques included multiple linear regression, t-test, F-test, correlation test, and the coefficient of determination. The results of the study show that motivation has a significant effect on employee performance with a significance value of p = 0.008. Organizational culture also has a significant influence on employee performance, with a significance level of p < 0.001. Simultaneously, motivation and organizational culture contribute significantly to employee performance, as evidenced by the coefficient of determination (R²) of 0.914 or 91.4%. These findings indicate that efforts to improve employee performance optimally can be achieved through proper management of work motivation and the strengthening of a positive, participative organizational culture that supports a healthy and productive work environment.